ISSUANCE OF BONDS AS A FİNANCİNG TOOL İN THE OİL İNDUSTRY OF AZERBAİJAN (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The issuance of bonds is one of the widely used financing methods in the fields of economics (fiscal policy) and finance (lending). Issued bonds play an invaluable role in forming both public and private sector projects and budgets through the use of low-interest loans, tax incentives, and the elimination of budget deficits. The main purpose of this article is to discuss the role and practical significance of bonds issued by the State Oil Company of Azerbaijan Republic (SOCAR) for the organization of modernization and reconstruction efforts in Azerbaijan’s oil industry (oil refining industry) since 2016. The main section of the article provides information on the nature of the modernization and reconstruction projects, as well as on the public bond offerings by SOCAR and other enterprises in the period following 2016. The practical importance of the article lies in its analysis and application of easy financing methods not only in the oil industry but also across other industrial and service sectors. Its theoretical significance lies, on one hand, in serving as a stimulus for future research of this kind, and on the other hand, in being a concise methodological guide for those who wish to learn about the structure and importance of bonds as a financial instrument. The scientific novelty of the article lies in the comprehensive analysis of fixed-income bond issuance, which is relatively new to the financial environment of Azerbaijan. The continuous occurrence of organized innovations in both the oil industry and the financial-credit sector can be considered a primary stimulus for writing such articles and dissertations.
Keywords: bond, fixed-income securities, SOCAR, oil industry, economic policy, finance-credit